A case of emergency stent graft placement for subclavian artery injury during ventriculoperitoneal shunt placement - Minoru Dote, MD; Shingo Hamaguchi, MD; Shoko Arizono, MD; Songhyon Cho, MD; Shinji Wada, MD; Shintaro Nawata, MD; Kazuki Hashimoto, MD; Hidefumi Mimura, MD (Radiology Case Reports)
With advancements in medical devices and imaging techniques, endovascular treatment using stent grafts has emerged as a viable and aggressive therapeutic option for traumatic subclavian artery injuries, including iatrogenic cases. Existing literature suggests that endovascular treatment is less invasive and offers hemostatic success rates comparable to traditional surgical methods. However, there is a paucity of case reports, necessitating further investigation into treatment indications and procedural challenges. We report the case of a 50-year-old woman who sustained a right subclavian artery injury during ventriculoperitoneal shunt placement, a rare occurrence of iatrogenic subclavian artery injury. In our approach, we utilized both the right common femoral artery and right radial artery to attempt a pull-through technique, although this was abandoned owing to radial artery spasm. Ultimately, a stent graft was successfully implanted by traversing the injury site with a micro-guidewire via the right common femoral artery. This case highlights the feasibility of endovascular treatment, even in rare injury mechanisms, provided that thorough preoperative and intraoperative imaging evaluations are performed.